Study MetheletetraHydrofolatredctase (MTHFR) Gene Polymorphism in Myocardial Infarction Patients in Babylon Province/ Iraq - Mona Al-Terehi (Journal of Global Pharma Technology, 2017)
The present study was aimed to investigate MetheletetraHydrofolatredctase (MTHFR) gene which related to acute myocardial infarction (MY) patients using restriction fragment length polymorphism (RFLP-PCR) technique, the results show that the homozygote TT genotype was (23.3%) in patients and (30.0%) in control with non-significant variation (OR 1.41). while CT genotype was (30.0%) and (33.03%) in patent and control respectively with not significantly with OR (14.414) , CC genotype was (46.7%) in patients and (36.70%) in control. The allelic frequency was T patient vs. controls; 38% vs. 47% while allelic frequency was C in the patient vs. controls; 62% vs. 53%. we have concluded that the MTHFR 677T allele hasn’t been contributed as a risk factor for myocardial infarction .Our findings raise the possibility that novel genetic defects and/or environmental factors may influence homocysteine metabolism in this ethnic group.Keywords: MetheletetraHydrofolatredctase, Acute myocardial infarction, RFLP-PCR.